2009
DOI: 10.1016/j.pbb.2008.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Contingent and non-contingent effects of low-dose ethanol on GABA neuron activity in the ventral tegmental area

Abstract: Ventral tegmental area (VTA) GABA neurons appear to be critical regulators of mesocorticolimbic dopamine (DA) neurotransmission, which has been implicated in alcohol reward. The aim of this study was to evaluate the effects of low-dose "non-contingent" intravenous (IV) ethanol (0.01-0.1 g/kg) on VTA GABA neuron firing rate and synaptic responses, as well as VTA GABA neuron firing rate during low-dose "contingent" IV ethanol selfadministration. Intravenous administration of 0.01-0.03 g/kg ethanol significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 42 publications
2
52
1
Order By: Relevance
“…In addition, a subset of VTA GABA receptors may be implicated in the development of addictive behavior. In particular, it has been reported that activation of central GABAergic neurotransmission (particularly through GABA B receptors of the VTA) is closely connected with mesolimbic dopaminergic neurotransmission during rewarding processes (Diana et al, 2003;Fadda et al, 2003;Steffensen et al, 2009).…”
Section: Gaba As a Therapeutic Target For Addictionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a subset of VTA GABA receptors may be implicated in the development of addictive behavior. In particular, it has been reported that activation of central GABAergic neurotransmission (particularly through GABA B receptors of the VTA) is closely connected with mesolimbic dopaminergic neurotransmission during rewarding processes (Diana et al, 2003;Fadda et al, 2003;Steffensen et al, 2009).…”
Section: Gaba As a Therapeutic Target For Addictionmentioning
confidence: 99%
“…Acute exposure to ethanol potentiates GABA A receptor function by complex effects on pre-and postsynaptic elements of GABAergic synapses (Fleming et al, 2009) and accordingly, induces a CNS depression secondary to enhanced inhibitory transmission. On the other hand, chronic ethanol exposure seems to induce compensatory adaptations to the acute facilitatory effects of ethanol on GABAergic synapses (Steffensen et al, 2009;Diana et al, 2003), such as marked changes in the expression of specific GABA A receptor subunits and alterations in the subunit composition of these receptors, which are primarily responsible for alterations in GABAergic signalling associated with chronic ethanol exposure (Weiner and Valenzuela, 2006). These adaptive changes are thought to lead to a pronounced hypofunction of GABAergic neurotransmission and possibly the development of tolerance to the effects of ethanol on these synapses (Weiner and Valenzuela, 2006).…”
Section: Gaba As a Therapeutic Target For Addictionmentioning
confidence: 99%
“…Social drinking can produce a low-to-moderate concentration of EtOH (≤30 mmol/L) in the brain. Animal studies have shown that a low dose of EtOH (0.01 g/kg, <10 mmol/L) applied to VTA could significantly increase GABA neuron firing rate and afferent-evoked synaptic responses [73] . Voluntary…”
Section: Effects Of Social Drinkingmentioning
confidence: 99%
“…In addition, a subset of VTA GABA A Rs is implicated in the development of addictive behavior. In particular, the activation of central GABAergic neurotransmission is linked to mesolimbic dopaminergic neurotransmission during rewarding processes [73,100,105] . We suggest that preclinical and clinical studies should place more emphasis on the GABAergic system as a pharmacotherapeutic target for the treatment of AUD.…”
Section: Effects Of Chronic Alcohol Consumptionmentioning
confidence: 99%
“…Studies using anesthetized rats demonstrated that low dose ethanol (0.01-0.03 g/kg) increases VTA GABA firing (Steffensen et al 2009), whereas higher doses of ethanol (0.2-2.0 g/kg) demonstrate an inhibition of GABAergic activity (Gallegos et al 1999). An electrophysiological study examined modulation of VTA DA neurons after chronic exposure to ethanol in C57BL/6J mice.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%